Pengaruh perbedaan jumlah umbi terhadap karakteristik kimia, antioksidan, dan total fenol bawang putih - Connie Daniela; Desni Siliawati Br Brahmana; Herla Rusmarilin (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Garlic is parental herbaceous plant that forms a bulb layer. There are two varieties of garlic in Indonesia, namely single tuber and compound tuber. Variety differences are based on plant size, number of flakes, and chemical content in the tuber. The aim of the study was to determine the chemical characteristics, total phenols, and antioxidant activity of both varieties garlic before or after drying. Making powder by drying garlic in an oven at 40oC for 48 hours. Garlic extraction with maceration method using ethanol. Fresh garlic and garlic powder were then analyzed for water content, ash content, fat content, protein content, antioxidant activity, and total phenols. Data analysis techniques used the SPSS 22 application. The results showed the water content of fresh garlic and compound and single garlic powder respectively, amounting to 63.767%, 56.722%, 4.671%, 5.179%. Ash content, respectively, amounted to 3.697%, 2.426%, 3.936%, 2.55%. Protein content levels, amounting to 2.414%, 2.818%, 1.378%, 2.164%. Fat content levels of 1.118%, 1.639%, 0.174%, 0.238%. The total phenols in fresh garlic and single and compound garlic powders were 1.066 μgGAE/mg, 0.806 μgGAE/mg, 0.3761 μgGAE/mg, 0.4986 μgGAE / mg, respectively. Antioxidants were 49.448 μg/ml, 44.943 μg/ml, 75.391 μg/ml, 62.822 μg/ml, respectively. Based on the results of the study different types garlic based on the number of tubers have an effect on water content, ash content, fat content, total phenol, antioxidant activity.